SISTEM KEPERCAYAAN KOMUNITAS ADAT TERPENCIL SUKU AKIT DI DESA PENYENGAT - ", Nurdianti; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Remote Area Community's Belief System of Akit Tribe in Desa PenyangatFaith is an aspect related to human belief to science, involving nature and human being. It can be related to religion concept or magical world or even not at all. Akit Tribe's belief is animism. Social change happen in Akit Tribe. Now, many of them are moslems,buddhist, and christian. The aim of this research is to find out the meaning and function of religion convertion and factors that cause religion switch in Akit Tribe Rwmote Community. Subject of this research is people of Desa Penyengat who decided to become christian. This is a descriptive qualitative research with purpossive technique sampling. In this research, writer found that in remote area, religion is a role in daily life. Factors that cause religion switch are: God's guideline, social environment, and certain religious even. Besides, missionary efforts gave a huge impact in this religion switch. The missionarist come to people's house directly and persuade them to switch the belief. Other factor of this switch is marriage with people from outside of Penyengat.Keyword: belief system, remote community, Religion convertion.